Compositional characteristics and health aspects of Hazelnut (Corylus avellana L.): an overview - Alasalvar, C. (2010)
Hazelnut (Corylus avellana L.) belongs to the Betulaceae family and is a popular tree nut worldwide, mainly distributed in the coasts of the Black Sea region of Turkey, southern Europe (Italy, Spain, Portugal, and France), and in some areas of the United States (Oregon and Washington). Hazelnut is also cultivated in some other countries such as New Zealand, China, Azerbaijan, Chile, Iran, and Georgia, among others.